Diversity of mechanisms to control bacterial GTP homeostasis by the mutually exclusive binding of adenine and guanine nucleotides to IMP dehydrogenase. (27th April 2022) - Fernández‐Justel, David; Marcos‐Alcalde, Íñigo; Abascal, Federico; Vidaña, Nerea; Gómez‐Puertas, Paulino; Jiménez, Alberto; Revuelta, José L.; Buey, Rubén M.
Abstract: IMP dehydrogenase(IMPDH) is an essential enzyme that catalyzes the rate‐limiting step in the guanine nucleotide pathway. In eukaryotic cells, GTP binding to the regulatory domain allosterically controls the activity of IMPDH by a mechanism that is fine‐tuned by post‐translational modifications and enzyme polymerization. Nonetheless, the mechanisms of regulation of IMPDH in bacterial cells remain unclear. Using biochemical, structural, and evolutionary analyses, we demonstrate that, in most bacterial phyla, (p)ppGpp compete with ATP to allosterically modulate IMPDH activity by binding to a, previously unrecognized, conserved high affinity pocket within the regulatory domain. This pocket was lost during the evolution of Proteobacteria, making their IMPDHs insensitive to these alarmones. Instead, most proteobacterial IMPDHs evolved to be directly modulated by the balance between ATP and GTP that compete for the same allosteric binding site. Altogether, we demonstrate that the activity of bacterial IMPDHs is allosterically modulated by a universally conserved nucleotide‐controlled conformational switch that has divergently evolved to adapt to the specific particularities of each organism. These results reconcile the reported data on the crosstalk between (p)ppGpp signaling and the guanine nucleotide biosynthetic pathway and reinforce the essential role of IMPDH allosteric regulation on bacterial GTP homeostasis. Abstract : PDB Code(s): 7PJI and 7PMZ ;